Optical phonon modes in 1:2 ordered trigonal Ba3MgNb2O9 perovskite: Synergy of both classical and quantum methods - Ferrer, Mateus M.; Sambrano, Julio R. [UNESP]; Hernandes, Antonio C.; Rodrigues, Joao E. F. S. (Wiley-Blackwell, 2020)
Ba3MgNb2O9 is a double perovskite niobate with a trigonal structure with space group D-3d(3). Such a niobium-based compound has a great potential for applications as microwave dielectrics in the telecommunication industry. In this work, we report the lattice dynamics calculation results using a Short-Range Force Field Model and Density Functional Theory to represent the optical phonon modes at Gamma-point of the Brillouin zone. The classical method uses the nearest neighbor interactions through the interatomic force constants to describe the local order for Raman and infrared spectra. At the same time, density functional theory methods took into account two functionals (PBE and B3LYP) in order to provide the optical modes through second derivatives of the total energy. In both methods, theoretical optical modes are in good agreement with reported experimental data. The combination of both classical and quantum theoretical methods provided basis for a systematic discussion on the origin of the optical modes including the prediction of the dielectric tensor. We believe that this work presents useful information about the structural and vibrational characterization of Ba3MgNb2O9 perovskite and possible targeting for its application as microwave dielectrics for the communication technology.
Keywords: Ba3MgNb2O9; density functional theory; dielectric tensor; lattice dynamics